AHP and GIS-Based Site Selection for a Sanitary Landfill: Case of Settat Province, Morocco - Ghizlane Benezzine (Polish Society of Ecological Engineering (PTIE), 2022)
In Morocco, solid household waste is often disposed of in open air in unsuitable sites causing adverse effects on humans and the environment. In the province of Settat, there are eight uncontrolled landfills. The present study aims to determine the most suitable sites from an environmental and economic point of view to ensure good management on a regional scale. Used a combination of a multi-criteria method (the AHP analytical hierarchy process) and a GIS geographic information system (ArcGIS) with ten criteria: distance from the ground water, water surfaces, drilling, settlements, forests, roads, highway, land use, slope, and elevation. The suitability map showed that about 18.5% of the study area is suitable for installing a sanitary landfill.